Mechanism of Action of the Sesquiterpene Compound Helenalin in Rhabdomyosarcoma Cells - Hakmin Mun; Helen Elizabeth Townley (MDPI AG, 2021)
Rhabdomyosarcoma (RMS) is the most frequent soft tissue sarcoma in paediatric patients. Relapsed or refractory RMS shows very low 5-year survival rates, which urgently necessitates new chemotherapy agents. Herein, the sesquiterpene lactone, helenalin, was investigated as a new potential therapeutic agent against the embryonal RMS (eRMS) and alveolar RMS (aRMS) cells. We have evaluated in vitro antiproliferative efficacy of helenalin on RMS cells by the MTT and wound healing assay, and estimated several cell death pathways by flow cytometry, confocal microscopy and immunoblotting. It was shown that helenalin was able to increase reactive oxygen species levels, decrease mitochondrial membrane potential, trigger endoplasmic reticulum stress and deactivate the NF-κB pathway. Confirmation was obtained through the use of antagonistic compounds which alleviated the effects of helenalin in the corresponding pathways. Our findings demonstrate that oxidative stress is the pivotal mechanism of action of helenalin in promoting RMS cell death in vitro.